Sexually Explicit Euphemism in Martin Amis’s Yellow Dog. Mitigation or Offence? - Eliecer Crespo Fernández (Miscelánea: A Journal of English and American Studies, 2006)
It is the purpose of this paper to provide an overview of the euphemistic modality that I shall call ‘explicit euphemism’ by means of an insight into the taboo of sex in Yellow Dog (2003) by Martin Amis. I argue that in today’s literary language euphemism moves away from the traditional approach to the phenomenon. Indeed, explicit and plain-spoken allusions to sexual issues fulfil the main function of euphemism insofar as they avoid linguistic items deemed unacceptable in social discourse, especially the so-called ‘four letter words’ related to sex. In this respect, Amis’s novel constitutes a representative example of the treatment that the realm of sex receives nowadays, in which it is difficult to draw the line between euphemism and dysphemism, between mitigation and offence. In order to give insight into the incidence of this euphemistic modality in today’s literary language, the final part of the article offers a glossary of the cases of sexually explicit euphemisms encountered in the novel aforementioned.